2017
DOI: 10.1038/srep42093
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Quantitative T1ρ-weighted Dynamic Glucose Enhanced MRI

Abstract: Common medical imaging techniques usually employ contrast agents that are chemically labeled, e.g. with radioisotopes in the case of PET, iodine in the case of CT or paramagnetic metals in the case of MRI to visualize the heterogeneity of the tumor microenvironment. Recently, it was shown that natural unlabeled D-glucose can be used as a nontoxic biodegradable contrast agent in Chemical Exchange sensitive Spin-Lock (CESL) magnetic resonance imaging (MRI) to detect the glucose uptake and potentially the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 31 publications
3
110
1
1
Order By: Relevance
“…Because of the complicated pathology and limited number of cases studied in this initial pilot study, it is difficult to determine the exact pattern of enhancement with glucoCEST. Others also found that regions of DGE and Gd enhancement differed in area . In our previous 7T study, we noticed in 1 patient case that early enhancement corresponded to the Gd‐enhanced ring, whereas later enhancement spread through a larger tumor area not enhanced in the Gd T 1 ‐weighted scan.…”
Section: Discussionmentioning
confidence: 70%
“…Because of the complicated pathology and limited number of cases studied in this initial pilot study, it is difficult to determine the exact pattern of enhancement with glucoCEST. Others also found that regions of DGE and Gd enhancement differed in area . In our previous 7T study, we noticed in 1 patient case that early enhancement corresponded to the Gd‐enhanced ring, whereas later enhancement spread through a larger tumor area not enhanced in the Gd T 1 ‐weighted scan.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, two CESL‐based DGE contrast metrics were investigated. First, the R 1ρ ‐weighted dynamic glucose‐enhanced (DGE ρ ) contrast calculated according to Schuenke et al:DGEnormalρfalse(normaltfalse)=normalS50msfalse(reffalse)-S50ms(t)normalS50msfalse(reffalse)·50ms,with S 50ms (t) being the acquired R 1ρ ‐weighted images for the spin‐lock time (TSL) = 50 ms (i.e., TSL 1 ), and S 50ms (ref) being the average of the first 20 S 50ms (t) images. Note, in comparison to the original definition, DGE ρ in Equation is divided by the respective TSL = 50 ms to enable a direct comparison of contrast values (in units of Hz) to the second DGE contrast metric investigated in this study (Equation ).…”
Section: Methodsmentioning
confidence: 99%
“…Whether glucose in blood vessels, extracellular glucose, or intracellular phosphorylated glucose derivatives are the driving source for the observed DGE contrast remains to be investigated in depth . Furthermore, the applicability for examinations in humans has already been verified in independent pilot studies based on glucoCEST and glucoCESL . However, DGE contrast maps are prone to motion‐induced artifacts because DGE image series consist of data acquired before, during, and after glucose injection.…”
Section: Introductionmentioning
confidence: 99%
“…Current CEST B 0 correction methods rely on data post‐processing and require either a separate field map acquisition or multiple acquisitions with a fine frequency interval to correct the shift in the CEST spectrum caused by zero‐order shim changes . Motion correction is performed retrospectively via rigid or nonrigid registration of CEST offset‐images. However, the CEST signal attenuation caused by geometric distortion because of gradient field variation cannot be corrected in this way.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of motion in CEST MRI is almost unexplored. The few studies that examine motion correction in CEST MRI are based either on rigid image registration or retrospective time domain analysis…”
Section: Introductionmentioning
confidence: 99%